BIOMETRIC CHARACTERISTICS AND STRESS LEVELS OF GLASS EEL (Anguilla sp.) IN THE SOUTHERN ESTUARIES OF SUKABUMI, WEST JAVA - Aulia Nur Larasati; Ridwan Affandi; Mohammad Mukhlis Kamal; Dudi Muhammad Wildan (Jurnal Teknologi Perikanan dan Kelautan)
Palabuhanratu Bay is the terminating flow for some rivers, i.e. the Cimandiri River, Ciletuh River, Cikaso River, and Cibuni River, where the estuary is the entry route for glass eels (Anguilla spp.) or fish seeds from sea waters to these estuaries. Different rivers have different water quality conditions that may imply differences in the quality and quantity of eels entering the estuary. This research aims to determine locations with superior seeds, and seeds with low quality based on studying biometric characteristics and stress levels of eel seeds in several estuaries in the south of Sukabumi, West Java. The information gathered is subject to determining the highly recommended use of glass eels as seeds in eel aquaculture, as well as determining the area where habitat rehabilitation and conservation. The research was carried out in four locations, namely the Cimandiri, Ciletuh, Cibuni, and Cikaso River Estuaries, from December 2021 to January 2022, the peak time for eel seed migration. The parameters observed include water physics and chemistry, biometrics, and blood glucose. The research results show that each location has different physical and chemical water parameter values but has relatively the same stress level. The best biometric value of eel fish seeds was found in eel seeds originating from the Cimandiri River, while the lowest one was at the mouth of the Cibuni River. Therefore, eels that are suitable for cultivation activities come from the Cimandiri River Estuary, while the eel location that needs conservation is the Cibuni River Estuary.